The Effect of Financial Management Training, Corporate Governance, and Strategic Financial Management on Company Value in the Digital Economy Era: A Systematic Literature Review (Prisma 2007–2025) - Pakpahan, Benhur; Bangun, Rehulina; Rosanti , Raina (Green Publisher Indonesia, 2025)
This study aims to systematically analyze the relationship between financial management training, corporate governance, and strategic financial management on increasing company value in the digital economy era. Using a Systematic Literature Review (SLR) approach based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, this study examines 18 scientific articles published in the period 2007–2025 from the Scopus, SSRN, DOAJ, and Google Scholar databases. From the initial 284 articles identified, 42 passed eligibility screening, and 18 were included in the final thematic synthesis. The distribution comprised 6 articles on financial training (33.3%), 5 articles on corporate governance (27.8%), 4 articles on strategic financial management (22.2%), and 3 articles on integrated frameworks (16.7%). The analysis results show that financial management training plays a significant role in increasing individual financial self-efficacy, which in turn strengthens the organization's strategic ability in managing financial resources. Good corporate governance has been shown to increase transparency, investor confidence, and market valuation, while digitally oriented strategic financial management strengthens the competitiveness and sustainability of company value. Conceptual synthesis reveals that these three factors interact synergistically, with digital transformation acting as a moderating variable that strengthens the relationship between financial strategy and company value. These findings enrich contemporary financial management literature and provide practical recommendations for organizations to integrate financial training, governance, and digital strategy in building long-term value.